Patterns of math and reading achievement in children and adolescents with autism spectrum disorder. (April 2022) - Bullen, Jennifer C.; Zajic, Matthew C.; McIntyre, Nancy; Solari, Emily; Mundy, Peter
Highlights: Study conducted a cluster analysis on math and reading abilities. Analyses revealed 2 subgroups characterized by differences on IQ and working memory. Reading fluency distinguished subgroups more powerfully than other variables. Findings have important implications for inclusion in general education. Abstract: Background: There has been an increase of autistic students without intellectual disabilities (autisticWoID ) placed in general education settings (Hussar et al., 2020), but there is a lack of understanding of how to best support classroom learning for these children. Previous research has pointed to subgroups of autisticWoID children who display difficulty with mathematics and reading achievement (Chen et al., 2018 ; Estes et al., 2011; Jones et al., 2009; Wei et al., 2015 ). Research has primarily focused on symptomatology and communication factors related to learning in subgroups of autistic children. The current study sought to expand upon this research by assessing the validity of these previous studies and by investigating the specific contribution of domain-general cognitive abilities to differences in these subgroups. Method: Seventy-eight autisticWoID individuals ( M = 11.34 years, SD = 2.14) completed measures of mathematics and reading achievement, IQ, working memory, inferential thinking, and Theory of Mind (ToM). A hierarchical cluster analysis was performed on the math and reading measures. Results: The analysis revealed two unique achievement groups: one group that performed lower than expected on math and reading achievement and a second group that performed higher than expected. Groups differed significantly on IQ and working memory and were distinguished by performance on reading fluency. Groups did not differ on ToM, inferential thinking, or symptomatology. Conclusion: These findings describe a group of autisticWoID individuals that may be more likely to experience difficulty learning, which should be accounted for in general education settings.